Perceptions of school teachers on the use of collaborative tools at school - Nunes, M.; Oliveira, A. (EDULEARN20 Proceedings, 2020)
Technology has changed many aspects of life in society, playing a key role in our quotidian, and having profound impacts on how we relate to our peers and the way we educate the youngest. Collaborative tools have broken the barriers of time and space, allowing us to collaborate without these constraints. There are numerous advantages in the use of these tools in secondary education both in the immediate and future lives of students. Thus, came the idea for this study: to understand the teachers' opinions about collaborative tools and what are role they play in the teaching-learning process, as a way to transmit knowledge and communicate, facilitating the interaction between teachers and students. The state of the art is addressed in relation to collaborative tools in schools, the advantages and possible deterrents to the use of this type of tools from the perspective of teachers. Based in previous studies, a questionnaire was elaborated to verify the opinions and perceptions of teachers. Results highlighted that teachers recognize the benefits of these tools but, at the same time, there are factors that function as limitations to their use. In fact, collaborative tools and ICT are still not well explored by teachers in the context of their work.